Identifikasi Lahan Gambut Menggunakan Citra Satelit Landsat 8 Oli Tirs Berbasis Sistem Informasi Geografis (SIG) Studi Kasus Pulau Tebing Tinggi - Akhbar Putra; Sigit Sutikno; Rinaldi Rinaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This paper presents the application of satellite remote sensing techniques to detect and identify peatland cover types in Riau Province, Indonesia. Mapping the spatial distribution of organic soils is important for decision making in land management and mitigation of peatland forest fires. Organic soil types have a strong effect on carbon storage, water availability and quality, biodiversity and many other ecosystem services. This study uses GIS software and Landsat-8 satellite data to identify the type of peat land cover in Tebing Tinggi island. This area were picked up as pilot project areas for this research, because these areas historically had many fire spots on last few years. The results show how this approach can be used to land cover classification and for predicting mineral and organic soils in locations within the map unit quickly and cost-effectively. The identification of Peatland was done using composites of band ratios and single band variables. The best composite band ratio that can be used is a 7-5-3 band combination. This combination consists of band 7 (Shortwave Infrared 2), band 5 (Near Infrared) and band 3 (Green). This combination is selected because it can classify land cover of peatland into 5 classes, there are primary peat swamp forest, disturbed / regrowth peat swamp forest, agriculture mosaic, burn scars or urban areas, missing data or water. The result of data processing of Landsat 8 Satellite image shows that 95% of Tebing Tinggi island area is composed of peatland. Based on the results of data processing Citra Landsat 8 can be seen some areas of Tebing Tinggi islands indicate red color means the area of burn scars or burn earth. The result of fire point processing shows the largest number of hotspots existed throughout the year 2014 with the number of fire points as much as 1351 points. In the year 2013 with the number of hotspots as much as 110 points and the smallest occurred throughout the year 2015 with the number of points of fire as much as 79 points. The result map peatlands will be useful for land management and carbon storage decisions in the soil in an effort to prevent land and forest fires. Keywords: GIS, remote sensing, peat, land cover, hotspot.